Adipophilin expression in cutaneous malignant melanoma. (22nd December 2016) - Fujimoto, Masakazu; Matsuzaki, Ibu; Yamamoto, Yuki; Yoshizawa, Akihiko; Warigaya, Kenji; Iwahashi, Yoshifumi; Kojima, Fumiyoshi; Furukawa, Fukumi; Murata, Shin‐ichi
Abstract : Background: The lipogenic pathway is upregulated in cancer cells, including melanomas. However, the pathological significance of cellular lipids in melanocytic lesions has yet to be determined. In this study, we evaluated intracytoplasmic lipid droplets in melanocytic nevi (MNs) and malignant melanomas via immunohistochemical analysis of adipophilin (ADP), which coats lipid droplets. Methods: One hundred primary cutaneous melanocytic lesions [33 MNs, 17 melanomas in situ (MIS), and 50 invasive melanomas (IMs)] were immunostained for ADP. The intensity score (IS) and proportion score (PS) of ADP staining in each case was recorded semiquantitatively on a scale of 0 to 3+. Results: High ADP expression (IS2/3+ and PS2/3+) was observed in 27 primary cutaneous melanocytic lesions that consisted of 23 IMs, three MISs, and one MN. Consequently, high ADP expression was associated with malignancy (38.8% vs. 3.0%; p < 0.0001). Among the IMs, high ADP expression was more prevalent in pT3/4 than pT1/2 (63.3% vs. 23.8%; p = 0.01) and Stage 3/4 than Stage 1/2 (76.9% vs. 36.8%; p = 0.02). Conclusions: The majority of the melanocytic lesions with high ADP expression were malignant melanomas in our cohort. Therefore, ADP expression may serve as a sensitive diagnostic marker for malignant melanoma.